Singapore as A Global City: Response to Urbanization, Climate Change, and Digital Economy - Sandiya, Idris; Nasrudin, Arief (UI Scholars Hub, 2025)
Background: Singapore faces pressures from rapid urbanization, climate change, and digital economic transformation amid limited land and resources. As both a city-state and global economic hub, Singapore develops adaptive strategies that balance growth, sustainability, and competitiveness through technology-driven governance and long-term planning. Aims: This study analyzes Singapore’s adaptation strategies in addressing urban, environmental, and digital economic challenges while evaluating policy effectiveness and limitations within the frameworks of the global city, state capitalism, and sustainability governance. Methods: A qualitative literature review and SWOT analysis were conducted using secondary data from academic journals and policy reports. The analysis focuses on the integration of spatial, environmental, and economic policies as instruments of global city adaptation. Results: Findings reveal three main pillars: environmental resilience through innovation, smart urbanization via smart city and transit-oriented development, and economic resilience through high-tech industrial diversification and nationwide digitalization. Policies such as carbon taxation, adaptive drainage, NEWater, and the Smart Nation Initiative have enhanced national competitiveness and resilience. Challenges remain—foreign labor dependence, high living costs, digital energy consumption, and social inequality due to automation. Conclusion: Singapore’s adaptive strategy positions it as a model smart sustainable global city in Asia. Through state control, technological innovation, and sustainability-oriented governance, Singapore expands the global city paradigm under state capitalism. The study implies that urban sustainability depends not only on technological and market efficiency but also on the capacity of state and society to foster adaptive, collaborative, and equitable governance.